Techniques used in high- and low-scoring hecht vaults performed at the 1995 World Gymnastics Championships - Takei, Y.; Dunn, J. H.; Blucker, E. P.; Nohara, H. (Journal of Applied Biomechanics, 2000)
The 25 highest scored Hecht vaults (G!) performed during the 1995 World Championships were compared with those receiving the 25 lowest scores (G2). Hypotheses were: GI would achieve (a) larger kinetic energy at takeoff from the board and the horse, (b) greater displacements of CM and greater forward body rotation in prellight. (c) greater changes in velocities and angular momentum on horse, (d) more rapid, forceful blocking/pushing off the horse, and (e) greater "amplitude" and better "form" during the post-flight than G2. A 16-mm motion picture camera, operating at 100 Hz. recorded the vaults during the compulsory competition. The results of t tests (p < .005) indicated Gl had (a) larger kinetic energy at takeoff from the board and the horse, (b) greater displacements of CM and greater forward body rotation in pre-flight. (c) greater changes in vertical velocity and angular momentum on the horse. greater vertical impulse of high force and short duration exerted on the horse, and greater "amplitude," greater backward body rotation, and greater body extension in post-flight than G2. In conclusion, successful performance of the Hecht vault is likely when focus is on sprinting the approach, blocking and pushing off the horse rapidly and vigorously downward, and maintaining the fully extended body position throughout the post-night to display "form" or fish-like body position for a virtuosity bonus point and simultaneously to prepare for a controlled landing on the mat.